2010
DOI: 10.1016/j.jalgebra.2009.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Singular plane curves with infinitely many Galois points

Abstract: For a plane curve C , we call a point P ∈ P 2 a Galois point with respect to C if the point projection from P induces a Galois extension of function fields. We give an example of a singular plane curve having infinitely many inner and outer Galois points. We also classify plane curves whose general points are inner Galois points. Before our results, known examples in the theory of Galois points have only finitely many Galois points, except trivial cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Recently, the present author [3] showed that δ(C) = 0, 1 or d for any other smooth curve C. As a next step, it would be nice to give an upper bound for δ(C) for all irreducible plane curves C. Miura [16] gave a certain inequality related to δ(C) if p = 0 and d − 1 is prime. The present author and T. Hasegawa [6] settled the case δ(C) = ∞. We call this case (FH).…”
Section: Introductionmentioning
confidence: 91%
“…Recently, the present author [3] showed that δ(C) = 0, 1 or d for any other smooth curve C. As a next step, it would be nice to give an upper bound for δ(C) for all irreducible plane curves C. Miura [16] gave a certain inequality related to δ(C) if p = 0 and d − 1 is prime. The present author and T. Hasegawa [6] settled the case δ(C) = ∞. We call this case (FH).…”
Section: Introductionmentioning
confidence: 91%
“…In [10] it is also proven that (C) is a non-empty Zariski open set of C if and only if C is projectively equivalent to the curve defined by X Z q−1 − Y q . More recently, in [9] plane curves with infinitely many outer Galois points are also classified.…”
Section: Plane Curves Having Infinitely Many Galois Pointsmentioning
confidence: 99%
“…Recently, Fukasawa and Hasegawa [10] found an example having infinitely many inner and outer Galois points.…”
Section: Plane Curves Having Infinitely Many Galois Pointsmentioning
confidence: 99%
“…x − y q = 0, where p > 0 and q is a power of p. Let P = (0 : 0 : 1) and let Q ∈ {Z = 0} \ {(1 : 0 : 0), (0 : 1 : 0)}. According to [4], P is an inner Galois point and Q is an outer Galois point. Note that there exists an inclusion G P ֒→ P GL(3, k) and G P fixes Q.…”
Section: Proof Of Theoremmentioning
confidence: 99%